The Transformational Leadership Management in Efforts to Improve Education Quality (A Multi-Case Study at SD Negeri Kiduldalem I and SD Swasta Nahdhatul Ulama Bangil, Pasuruan Regency) - Laila Novida; Ahmad Thohirin; A. Faizin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The leadership of school principals is a strategic factor in improving the quality of education at elementary schools. Various studies have shown that transformational leadership has a positive influence on teacher performance and the quality of learning. However, most studies still focus on leadership styles and have not examined transformational leadership as a structured managerial process. This study aims to analyze the management of transformational leadership by school principals in efforts to improve the quality of education at elementary schools through a multi-site study approach. The research employs a qualitative approach with a phenomenological design at two elementary schools, namely SD Negeri Kiduldalem 1 Bangil and SD Swasta Nahdlatul Ulama Bangil, Pasuruan Regency. Data collection techniques included in-depth interviews, observations, and documentation. Data analysis was conducted using the Miles and Huberman interactive model. The results show that the school principals apply transformational leadership through quality program planning, human resource organization, supportive academic supervision, and continuous evaluation. Differences in the context of public and private schools affect managerial flexibility; however, both schools demonstrate the significant contribution of transformational leadership to improving the quality of education. This study concludes that systematic and contextual management of transformational leadership can be the main driver of improving elementary school education quality.